Integrated Neuroscience - Marcus, Elliott M.; Jacobson, Stanley (Springer, 2002)
This textbook takes as a premise that, in order to make intelligent diagnosis and provide a rational treatment in disorders of the nervous system, it is necessary to develop the capacity to answer the basic questions of clinical neurology: (1) Where is the disease process located? (2) What is the nature of the disease process? The purpose of this textbook is to enable the medical student to acquire the basic information of the neurosciences and neurology and most importantly the ability to apply that information to the solution of clinical problems. The authors also suggest that hospital trips be a part of any Clinical Neurosciences Course so that the student can put into actual practice what he has learned in the classroom. We believe that this textbook will be of value to the student throughout the four years of the medical school curriculum. Medical, psychiatry and neurology residents may also find this text of value as an introduction or review. It is more true in neurology than in any other system of medicine that a firm knowledge of basic science material, that is, the anatomy, physiology and pathology of the nervous system, enables the student and physician to readily arrive at the diagnosis of where the disease process is located and the nature of the most likely pathology. Subsequently that knowledge may be applied to problem solving in clinical situations. The two authors have a long experience in teaching neuroscience courses at the first or second year medical student level in which clinical information and clinical problem solving are integral to the course. In addition the first author has developed a case history problem solving seminar in which all medical students at the University of Massachusetts participate during their clinical neurology clerkship rotation. This provides the students an opportunity to refresh their problem solving skills and to review and update that basic science material essential for clinical neurology. The second author has had extensive experience in utilizing sections of this text in neuroscience courses for advanced undergraduate college students and ancillary health profession students. At these several levels, we have observed that this approach reinforces the subject matter learned by markedly increasing the interest of the students in both basic and clinical science material. This text is an updated version of an earlier integrated textbook originally developed by the authors along with Dr Brian Curtis and published by W. B. Saunders in 1972 as "An Introduction to the Neurosciences". The present text provides an updated approach to lesion localization in neurology, utilizing the techniques of computerized axial tomography (CT scanning), magnetic resonance imaging (MRI) and magnetic resonance angiography (MRA) that were not available in 1972. In addition, the other modem clinical techniques of evoked potentials, positron emission tomography (PET), single photon emission computerized tomography (SPECT) and functional MRI neuroimaging are discussed and illustrated. Multiple illustrations demonstrating the value of these techniques in clinical neurology and neuroanatomical localization have been provided. The clinical case illustrations have been utilized both in the body of the text and in special problem solving chapters.
A Clinical Problem Solving Approach
Keywords: Neurosciences.; Nervous system—Diseases